PANDANGAN KI HAJAR DEWANTARA DALAM MENGKONSTRUKSI PENDIDIKAN INDONESIA PADA ABAD 21 - Iwan Sunarya; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Bajang Institute, 2022)
Education is an effort to liberate oneself in an effort to continue the culture and idiology of a generation in the next generation. The continuity of the educational and cultural relay that occurs will give birth to a national character. A valued nation is a nation that has exclusive characteristics so that it can live in the global diversity of the world. This characteristic will be self-efficacy of the challenges of the times faced by a generation of nations. Ki Hajar Dewantara as the main foundation of the philosophy of education in Indonesia holds the main key, when his down-to-earth thinking ideas continue to be maintained, alive and continue to grow amid the challenges of globalization. How is the idiology of KHD education in its role in constructing Indonesian Education in the 21st century to prepare the golden generation of 2045? This research uses a philosophical approach and literature review. Iiteratur sources are articles obtained from the Google Scholar database in journals in. Indonesia in 2018-2022. From the author's analysis of Ki Hajar Dewantara's thoughts, it can be concluded that education is not only centered on the development of knowledge and skills but also on the formation of children's character performance which is the responsibility of the family, school and community environment as an educational ecosystem. The system approach and the teachings of understanding, ngrasa and nglakoni in the process are carried out to guide students to grow according to the nature of nature and the times.